Educational interventions and contextual factors for optimising antibiotic prescription in paediatric uncomplicated acute respiratory tract infections in primary care: scoping review of reviews - Usue Elizondo-Alzola; Claudio Rocha; Leire Leache; Montserrat León-García; Luis Carlos Saiz; Ivan Solà; Camila Montesinos-Guevara; Adriana-Gabriela Meade; Andrea Boldú; Ignasi Bolíbar; Ena Niño-de-Guzmán; Pablo Alonso-Coello (BMC Pediatrics)
Abstract Background Inappropriate antibiotic prescription in paediatric uncomplicated acute respiratory tract infections (ARTIs) in primary care (PC) settings contributes to antimicrobial resistance. We aimed (1) to identify and describe educational interventions and their components to optimise antibiotic prescription for paediatric uncomplicated ARTIs in PC, and (2) to map contextual factors that may influence antibiotic prescription and the implementation of interventions. Methods We searched three electronic databases (Medline, CINAHL and Epistemonikos) to identify reviews on the effectiveness of educational interventions and contextual factors, for optimising antibiotic prescription (Concept) in paediatric uncomplicated ARTIs (Population) in PC (Context). We included reviews that reported explicitly the search strategy used. Two previously calibrated reviewers independently screened the literature, extracted data, and assessed the methodological limitations. We applied the “best-fit framework synthesis approach”, based on the main constructs of the Consolidated Framework for Implementation Research, and coded the data deductively by groups of analysis for reviews reporting effectiveness (e.g. antibiotic or consultation rate) or by thematic synthesis for reviews reporting contextual factors (e.g. healthcare professionals’ knowledge) based on a logic model. Results We identified 11 reviews evaluating education intervention and their characteristics, including 182 interventions with at least one educational component (educational intervention plus another type, educational or non-educational), with 136 providing information on characteristics and effectiveness. Successful interventions’ characteristics were related to the kind of intervention (e.g. communication skill training), mode of delivery (e.g. face to face), and target population (e.g. parents/caregivers). From the 22 reviews on contextual factors, healthcare professionals’ attitudes and perceptions, knowledge, and health system and professionals’ teams’ organization (inner setting), were the most frequent themes; less information was available on individuals´ characteristics (parents/children) and on outer setting (e.g. policies). Conclusion We identified a large number of heterogeneous educational interventions. Combining educational interventions plus another type targeting both parents/caregivers and healthcare professionals, and considering their needs and their context may improve antibiotic prescribing in children. Further research is needed on consultation rate, knowledge, attitudes, and satisfaction outcomes and contextual factors, as well as on the cost-effectiveness of the interventions. Registration The protocol was published in OSF iRegistries in May 2021 (Elizondo-Alzola, U).